Literature review and analysis of the social impact of a just energy transition - Sun, Zhonggen; Zhang, Furong; Wang, Yifei; Shao, Ziting (Frontiers in Sustainable Food Systems, 2023)
The energy transition is now the focus of global attention. This transition will have a significant impact on the global energy system as well as the political and economic landscape. Research on the social impact of the energy transition can help us get a deeper understanding of the energy transition and propose suggestions for future development. This paper focuses on the history and characteristics of the social impact evaluation of the energy transition, using bibliometric methods and the Web of Science Core Collection database with the help of HistCite and VOSviewer analysis tools. This paper discusses what is energy transition, just energy transition and its social impact and how to assess social impacts of just energy transition. In order to reduce the negative impacts of energy transition, interdisciplinary research, social impact research and social impact assessment of construction projects are three directions to be discussed.The study find that existing research mainly focuses on the connotation, pathways and different types of a just energy transition. There are three hot areas of research on the impact of a just energy transition: the sustainable development of energy, political economy and society. There is a general lack of research on the social impact of a just energy transition and an even greater lack of relevant research on social impact evaluation. Based on the global goal of just energy transition, this paper makes specific recommendations on what developed and developing countries, as well as sectors and enterprises within countries, should do.